Isolation and Genetic Characterization of a Tembusu Virus Strain Isolated From Mosquitoes in Shandong, China. Issue 2 (27th May 2013) - Tang, Y.; Diao, Y.; Chen, H.; Ou, Q.; Liu, X.; Gao, X.; Yu, C.; Wang, L.
Summary Tembusu virus (TMUV) is a flavivirus, presumed to be a mosquito‐borne flavivirus of the Ntaya virus subgroup. To date, however, there have been no reports indicating that mosquitoes are involved in the spread of TMUV. In this study, we report the first isolation of TMUV from Culex mosquitoes. We describe the isolation and characterization of a field strain of TMUV from mosquitoes collected in Shandong Province, China. The virus isolate, named TMUV‐SDMS, grows well in mosquito cell line C6/36, in Vero and duck embryo fibroblast (DEF) cell lines, and causes significant cytopathic effects in these cell cultures. The TMUV‐SDMS genome is a single‐stranded RNA, 10 989 nt in length, consisting of a single open reading frame encoding a polyprotein of 3410 amino acids, with 5′ and 3′ untranslated regions of 142 and 617 nt, respectively. Phylogenetic analysis of the E and NS5 genes revealed that the TMUV‐SDMS is closely related to the TMUV YY5 and BYD strains which cause severe egg‐drop in ducks. The 3′NTR of TMUV‐SDMS contains two pairs of tandem repeat CS and one non‐duplicate CS, which have sequence similarities to the same repeats in the YY5 and BYD strains. Our findings indicate that mosquitoes carrying the TMUV may play an important role in the spread of this virus and in disease outbreak.